Fall Prevention Education to Reduce Fall Risk on Elderly People - Ika Guslanda Bustam (IKesT Muhammadiyah Palembang, 2021)
This community service is carried out by providing education to reduce the risk of falling in the elderly in Kecamatan Sukarami, Palembang. This is expected to help and prevent and reduce the risk of falls that often occur in the elderly. Education is delivered by way of material presentation, and distribution of pamphlets. Before being given education for the elderly, several questions will be given, then they will be evaluated with the same questions to see the success of the education that the author has done. The results of this activity there is an increase in knowledge in the elderly about the risk of falling, namely as many as 15 elderly know the risk of falling well, then the elderly with moderate knowledge are 1 elderly. All participants are able to carry out activities both inside and outside the home without the need for tools or assistance from others